The Language of Philosophy and the Philosophy of Language: a Symbiotic Paradigm - Bassey Ekpenyong; Ephraim A Ikegbu (Budapest International Research and Critics University, 2018)
This paper was focused on the relationship between the discipline of Philosophy and Language: an interplay that has been found to be a sublime in terms of the conceptual methodological and classificatory values. The logic, objectivity, analytics, symbolism and universalism that have informed the study of language draw on the legacies of philosophy while on the other hand, philosophical studies gain ascendancy in elucidation from the expository, referential and concextual resources of language. It is recommended that experts on the two subjects should carry out more collaborative studies to explore the mutual insights available in the domains.